2018
DOI: 10.1159/000485888
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Rhegmatogenous Retinal Detachment Associated with Asteroid Hyalosis

Abstract: Background: To report two cases of rhegmatogenous retinal detachment (RRD) associated with asteroid hyalosis (AH). Case Presentation: Two patients presented with RRD originating from a flap tear. Case 1 involved a 62-year-old male who was found to have bullous RRD in his left eye originating from a flap tear. During vitreous surgery, a thick vitreous cortex was found to have strongly adhered to the entire retinal surface, from the center to the periphery. A bimanual method was then used in conjunction with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Bergren [ 3 ] and coworkers performed a cross-sectional study of 12,205 patients and reported patients with AH were more hyperopic than control subjects. Studies have shown that patient with AH presented with stronger vitreoretinal adhesion [ 18 , 19 ]. One explanation is that the complete posterior vitreoretinal interface may be important for the formation of asteroid zona pellucida.…”
Section: Discussionmentioning
confidence: 99%
“…Bergren [ 3 ] and coworkers performed a cross-sectional study of 12,205 patients and reported patients with AH were more hyperopic than control subjects. Studies have shown that patient with AH presented with stronger vitreoretinal adhesion [ 18 , 19 ]. One explanation is that the complete posterior vitreoretinal interface may be important for the formation of asteroid zona pellucida.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of asteroid hyalosis has been infrequently associated with causing complications, including calcified intraocular silicone lenses 1 and rhegmatogenous retinal detachments. 2 Abnormalities of the vitreoretinal surface in the setting of asteroid hyalosis do not necessarily dictate a negative vitrectomy prognosis 3 but can occasionally cause complications. We present a case illustrating enlargement of a full-thickness macular hole during surgical repair in a patient with very strong vitreoretinal adhesions around the macular hole and asteroid hyalosis.…”
mentioning
confidence: 99%